2021
DOI: 10.1126/sciadv.abd7851
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immunological phenotype signature-based high-throughput screening for the discovery of combination immunotherapy compounds

Abstract: Combination immunotherapy is promising to overcome the limited objective response rates of immune checkpoint blockade (ICB) therapy. Here, a tumor immunological phenotype (TIP) gene signature and high-throughput sequencing–based high-throughput screening (HTS2) were combined to identify combination immunotherapy compounds. We firstly defined a TIP gene signature distinguishing “cold” tumors from “hot” tumors. After screening thousands of compounds, we identified that aurora kinase inhibitors (AKIs) could repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
(117 reference statements)
1
48
0
Order By: Relevance
“…The increasing power and decreasing cost with deep sequencing technologies have enabled multi-dimensional analyses of gene expression. By coupling high throughput screening with high throughput sequencing (HTS 2 ), it is possible to utilize a specific set of genes as a surrogate for specific cellular activities in chemical and genomic screens 8,9 . By monitoring hundred or even thousand functional readouts, such “ultrahigh-content” screens offer numerous advantages over traditional one-dimensional screens, among which include the ability to deduce gene networks directly from the primary screen results and the feasibility to perform a drug screen without relying on a pre-defined druggable target 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing power and decreasing cost with deep sequencing technologies have enabled multi-dimensional analyses of gene expression. By coupling high throughput screening with high throughput sequencing (HTS 2 ), it is possible to utilize a specific set of genes as a surrogate for specific cellular activities in chemical and genomic screens 8,9 . By monitoring hundred or even thousand functional readouts, such “ultrahigh-content” screens offer numerous advantages over traditional one-dimensional screens, among which include the ability to deduce gene networks directly from the primary screen results and the feasibility to perform a drug screen without relying on a pre-defined druggable target 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…By coupling high throughput screening with high throughput sequencing (HTS 2 ), it is possible to utilize a specific set of genes as a surrogate for specific cellular activities in chemical and genomic screens 8,9 . By monitoring hundred or even thousand functional readouts, such “ultrahigh-content” screens offer numerous advantages over traditional one-dimensional screens, among which include the ability to deduce gene networks directly from the primary screen results and the feasibility to perform a drug screen without relying on a pre-defined druggable target 8,9 . More recently, we have extended the HTS 2 approach to a genome-wide screen by scoring hundreds of alternative splicing events to identify global splicing regulators 23 , illustrating a two-dimensional screen strategy that can be adapted to study many different paradigms in regulated gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with this gene signature, HTS 2 technology was applied for the identification of immunotherapy combination agents in TNBC. The results showed that aurora kinase inhibitors reprogram the expression of TIP gene signature and thus promote effective Tcell infiltration into the tumor microenvironment, significantly improving anti-programmed cell death 1 (PD-1) efficacy in preclinical models (51).…”
Section: The Application Of Hts 2 In Cancer Drug Discovery By Targeting Transcriptional Reprogrammingmentioning
confidence: 99%
“…Recently, a conserved stroma-immune relationship has been identified in 20 different cancers, and this relationship is capable of playing a prognostic role in response to ICI-based immunotherapy [23]. Additionally, alterations in both the adhesion molecules in endothelial cells and the chemokine-based axis can strongly influence T cell homing into the tumour [24][25][26]. The lack of expression of costimulatory receptors and the downregulation of major histocompatibility complex (MHC) molecules on the surface of tumour cells can affect TIL activation [27].…”
Section: Introductionmentioning
confidence: 99%